THE IMPACT OF RELIGIOUS HETEROGENEITY AND DEMOCRACY ON PUBLIC HEALTH EXPENDITURE: A PANEL CROSS-COUNTRY ANALYSIS - Leong Joe Wai; Muzafar Shah Habibullah (Journal of Islamic, Social, Economics and Development, 2019)
Public health expenditure is an important financial mechanism involve inmaintaining and improving the public’s health. Most spending relates to providing long-termcare, curative or rehabilitative care, medical goods and preventive care. Therefore, theprovision of public health service is essential for socio-economic development. Despite the linksbetween public health expenditure and ethnic heterogeneity having been intensively studied,very little effort has been devoted to investigating the combined effects of democracy and ethnicheterogeneity on public health expenditure. Religious differentiation can lead to different policypreferences among the people; thus, democratic governments might devote greater resourcesin order to address the preferences of each group. The purpose of this paper is to investigatethe effects of democracy and ethnic heterogeneity on public health expenditures. Using theGMM method developed by Arellano and Bond (1991) and data covering 124 countries for theperiod 1995 to 2015, we investigate whether a democratic country would devote larger publichealth expenditures in the presence of ethnic heterogeneity. Using this approach, the resultsindicate that the presence of ethnic heterogeneity in democratic country may lead to an increasein public health expenditure.